(untitled) (Research, Society and Development, 2020)
In this work, the capacity to remove ammonia nitrogen from landfill leachate previously diluted by Chlorella sp. immobilized in polymeric matrices of alginate/chitosan (AG/QT) and calcium alginate (AG). Two treatment systems were evaluated, one with tubular bioreactors fed with a substrate consisting of landfill leachate (LAS) in natura plus domestic sewage (ED) and another system consisting of conical bioreactors, having LAS substrate diluted in distilled water. The tests were carried out in batch mode at 27º C and luminance of 85 µE.s-1.m-2. The MEV and EDS analyzes of the surface of the spheres indicated that the support structure has porosity and retains the cells inside. Efficiencies of 40% ammoniacal nitrogen removal were observed after 4 hours of treatment of the LAS/ED substrate with microalgae immobilized in AG/QT. In the trials of Chlorella sp. immobilized in AG, removal efficiencies between 81 and 97% were recorded after 2 hours of treatment of the LAS substrate diluted in distilled water. In addition, Chlorella sp. presented efficiency of removal of N-ammonia from LAS diluted in distilled water in the range of 49 to 98% with increments of dissolved oxygen of up to 192% in 5 h of monitoring. These results indicate significant advantages of using immobilized microalgae for the treatment of wastewater, both in terms of resource recovery and recycling, and in relation to the potential phytoremediation of Chlorella sp. in the removal of ammoniacal nitrogen from landfill leachate.